Nedaplatin: A Radiosensitizing Agent for Patients with Cervical Cancer. (31st August 2010) - Mabuchi, Seiji; Kimura, Tadashi
Abstract : Despite the recent advances in the management of cervical cancer using cisplatin-based concurrent chemoradiotherapy, substantial treatment failure still occurs, especially in advanced-stage patients and early-stage cervical cancer patients with high-risk prognostic factors. Therefore, efforts to further improve the survival and quality of life of these patients are necessary. Nedaplatin (cis-diammine-glycoplatinum), a derivative of cisplatin, was developed with the aim of producing a treatment with a similar effectiveness to cisplatin but decreased renal and gastrointestinal toxicities. Based on the promising results of preclinical studies, the clinical efficacy of nedaplatin as a radiosensitizing agent was evaluated in patients with cervical cancer. Retrospective analysis of nedaplatin-based concurrent chemoradiotherapy (CCRT) against cervical cancer suggested that nedaplatin-based CCRT can be considered as an alternative to cisplatin-based CCRT in both early-stage and advanced-stage cervical cancer patients. However, due to the lack of a randomized controlled study, nedaplatin-based CCRT has not been convincingly proven to be clinically effective in patients with cervical cancer. Further investigations in randomized controlled trials are therefore needed.